Demographic profile of patients with acute poisoning in the emergency department of a tertiary care center and their outcomes - Sherpa, Mingmar Chhirring; Nakarmi, Rajan Narayan; Nepal, Suresh Prasad; K.C., Samir; Gupta, Sandeep; Bajracharya, Sunny; Pun, Soosita (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Acute poisoning is a major public health issue in Nepal, driving emergency visits, admissions, and deaths mainly from accessible organophosphorus pesticides. Patterns vary by region, with insecticides dominant in developing areas like Nepal, unlike pharmaceuticals in high-income countries. Limited recent prospective data from Nepalese tertiary centers prompted this study to profile demographics, agents, and outcomes. Methods: A prospective observational study was conducted at Bir Hospital Emergency Department, wards, and intensive care units from July to December 2025. The study included 238 patients aged 14 years and above with acute poisoning. A structured pro forma was used to collect data on demographic variables, poisoning agents, timing, and outcomes. Data analysis was performed using SPSS version 16, employing descriptive statistics and chi-square tests, with a significance level set at p<0.05. Results: Females constitute133(55.9%) of the population, with a peak incidence in the 15-25 years age group (37.4%). The majority are unmarried (64.7%) and students (38.7%). The prevalence of suicidal behavior is 83.2%, with the primary agents being Dichlorvos (29%) and Cypermethrin (24.4%). The mortality rate stands at 19(8%). Significant associations were observed between age and type (χ²=65.08, p<0.001), gender and type (χ²=25.33, p<0.001), and between arrival time and mortality (χ²=33.2, p<0.001), with a better prognosis when arrival occurred within 2 hours. Conclusion: Young females are suicidal with organophosphorus; early care is key to survival; urge mental health/pesticide controls.